ABOUT THE UNIVERSAL TECHNOLOGY OF PROCESSING JERUSALEM ARTICHOKE AND CHICORY FOR INULIN - T. S. Puchkova; D. M. Pikhalo; O. M. Karasyova (Пищевые системы, 2019)
The purpose of this work is development of the universal technology of processing of a girasol and chicory for an inulin according to requirements to quality of a feed stock. An inulin — the reserve carbohydrate widespread in flora. There is the most of inulin quantity in chicory, a girasol, much less is in onions, garlic, inula, yakena, etc. The inulin is widely applied as a low-calorie product in a dietary and diabetic food, just also as a jelly former in food. In the All-Russian Research Institute of Starch Products there are conducted researches on development of the universal technology for an inulin from inulin-containing raw materials. The technological assessment of a girasol and chicory from various regions of the Russian Federation is carried out, their physical and chemical indexes are defined. Requirements to processing behavior of raw materials are developed for inulin processing. By results of researches initial requirements to inulin-containing raw materials are defined: a mass fraction of dry solids is not less than 25 %, an inulin is not less than 16 %; mono — and disaccharides are 2 %. Diffusion from freshly harvested and dry chicory shavings and a girasol is studied, optimal established conditions are temperature 80–85ºC; the hydromodule for dry shaving — 1:7; for crude one — 1:2. It is developed the purification mode for extract and girasol and chicory syrups with use of various adsorbents such as the fissile coal, ion-exchange resins. The established high extent of extract and syrup purification is resulted in considerable decrease in a chromacity, mass fraction of a protein, ashes, etc. For researches as control specimens there was used an inulin of the foreign companies. Significance of the work is the creation of domestic technology of an inulin as prebiotic component for a treatmentand-prophylactic nutrition of the population and ensuring its import substitution.